Site specific mutagenesis: insertion of single noncomplementary nucleotides at specified sites by error-directed DNA polymerization. - Zakour, R A (1984)
We have utilized infidelity of DNA synthesis as a basis for site-directed mutagenesis. Both an endonuclease restriction fragment and a synthetic oligonucleotide were used as primers. DNA polymerase from bacteriophage T4 was used to elongate primer termini to a position immediately adjacent to two different preselected positions on phiX174 DNA templates. Then, the error-prone DNA polymerase from avian myeloblastosis virus was used to insert single non-complementary nucleotides at the designated positions at high efficiency. DNA sequence analysis confirmed that the mutant phage produced as a result of each site-specific mutagenesis reaction contained the nucleotide that was complementary to the one provided during the DNA copying reaction. The general applicability of this methodology to cloned DNAs will be discussed.